TAMBANG RAKYAT RENTAN KONFLIK (STUDI KASUS PERTAMBANGAN EMAS RAKYAT DI GUNONG UJEUN KABUPATEN ACEH JAYA) - Aminah Aminah (Universitas Teuku Umar, 2017)
This study aims to explain the gold miningarea in in Gunong Ujeun, Aceh jaya by using the theories of Thomas Homer-Dixon of the environmental scarcity. The data in this research was obtained through literature (library research) and field research. The research literature is done by reading textbooks, legislation, and other reading materials related to this research. While the field research conducted by interviewing informants.The results showed that the gold mining of people in Gunong Ujeun district of Aceh Jaya district is vulnerable to conflict. Theconflict that occurred in the Gunong Ujeun area is a horizontal latent conflict between the immigrant community and the local community. The causes of conflict are (1) logging in Gunong Ujeun (2) more difficult to get fresh fish. (3) Environmental pollution resulting from the use of mercury and cyanide. If the cause of the conflict is not well managed then it is feared that it will have an impact on the brutal conflict or even lead to acts of violence between migrantminers and local communities surrounding the gold mining areas that are disturbed by the security and comfort. Keywords: Conflict, environmental degradationand Peoples Mining.